Prioritizing Continuous Education Needs in the field of Guidance Counselling - Valenciano Canet, Grettel (2020)
This study looks at guidance counselors, who graduated with a BA from the University of Costa Rica and received extension courses or continuing education to remain abreast of the latest developments in their profession during 2011 to 2015. A quantitative research methodology with a descriptive scope was employed and a survey designed for purposes of data collection. The results were analyzed descriptively using frequencies and percentages. The study variable corresponds to the training needs of the guidance counselors selected for this study who met the inclusion criteria. Other considerations included academic and work-related aspects as well as topics of interest related to the field of guidance and counselling. Various training areas such as vocational, work, group, family, school, prison, law research, community, human development and interculturality in order to achieve a high level of competence and, as a result, learn about their continuous education needs, identify and select relevant topics for training purposes.  The selected activities were prioritized based on the opinions of the study participants, specific topics and themes and were taught in both a face-to-face setting as well as online course.  Courses included Family, Community, Vocational, Labor, School an, Personal Guidance Counselling, among others. The counselors are able to continue receiving continuing education courses indefinitely, in order to strengthen areas to improve their performance and learning new skills required to adapt to different labor contexts and address the social needs of others as Counsellors.